Knowledge of the Brain Death Concept by Personnel in Spanish and Latin-American Healthcare Centers. Issue 4 (April 2014) - Ríos, Antonio; López-Navas, Ana Isabel; Ayala-García, Marcos A.; Sebastián, Maria José; Abdo-Cuza, Anselmo; Alán, Jeannina; Martínez-Alarcón, Laura; Ramírez, Ector Jaime; Muñoz, Gerardo; Palacios, Gerardo; Suárez-López, Juliette; Castellanos, Ricardo; et al.
Background: The knowledge and acceptance of the concept of brain death (BD) among health care personnel is fundamental. Objective: To analyze the level of understanding of the BD concept among personnel in Spanish and Latin American healthcare centers and to determine the factors affecting this attitude. Material and methods: Data from 12 hospitals and 32 primary care centers in 4 countries within the International Collaborative Donor Project were selected (Spain, Mexico, Cuba and Costa Rica (n = 4378)). Results: 62% of the personnel (n = 2714) understood BD and believed that this was the death of an individual. Of the rest, 30% (n = 1 333) did not understand it and the remaining 8% (n = 331) believed it did not mean the death of a patient. 83% (n = 931) of physicians understood BD, compared to 75% (n = 895) of nurses, 55% (n = 299) of healthcare assistants, 53% (n = 108) of non-healthcare university-educated personnel and 36% (n = 481) of those without a university education (p<0.001). 68% (n = 1084) of Mexicans understood BD compared to 66% (n = 134) of Cubans, 58% (n = 1411) of Spaniards, and 52% (n = 85) (p<0.001) of Costa Ricans. There were significant relationships between knowledge of the concept and the following: type of healthcare center (p<0.001), clinical service (p<0.001), having spoken about organ donation within the family (p<0.001) and one's partner's attitude to the subject (p<0.001). A direct relationship has been found between understanding the concept and attitude toward deceased donation (p<0.001). Conclusions: The understanding of BD by personnel from healthcare centers was not as good as expected. There were marked differences depending on job category.